Game-Based Assessment of School Readiness Domains of 3-8-year-old-children: A Scoping Review - Stephen Amukune; Karen Caplovitz Barrett; Krisztián Józsa (Springer, 2022)
Precise assessment of school readiness is critical because it has practical and theoretical implications for children's school and life success. However, school readiness assessment mainly relies on teacher reports and a few direct evaluations requiring a trained examiner. Studies indicate that 80% of games and apps target preschool children and education, suggesting that apps are familiar and fun for this age group. Previous reviews have focused on these apps' training capability but not on their assessment of school readiness. This Scoping review examines 31 studies published from 2011-2019. The Evidence Centred Design (ECD) framework was used to evaluate game-based assessment (GBA) suitability to assess school readiness domains. Results show that it is possible to assess school readiness using GBA. Most studies assessed cognitive domains in school settings and adopted an external assessment of the tasks. However, most studies only evaluated one competency, and few intervention strategies targeted the enhancement of school readiness. Besides, few studies followed the ECD framework strictly. Implications include expanding the assessment to other school readiness domains with a real-time inbuilt assessment that conforms to the ECD framework. GBA provides a new approach to assess school readiness outside or inside the school settings in this online era.